O-28 Evaluating the systematic implementation of the 'let me decide' programme in long term care: A user's perspective. (1st September 2015) - O'Farrell, Irene; Cornally, N; McGlade, C; Weathers, Elizabeth; Daly, Edel; Fitzgerald, Carol; O'Caoimh, Rónán; Coffey, Alice; Molloy, D William
Abstract : Background: The 'Let Me Decide' Advance Care Planning programme (LMD-ACP) offers a structured approach to End- of- Life (EoL) care planning in long-term care for both residents with and without capacity to complete an advance care directive/plan. The programme was implemented into three homes in the South of Ireland. Aim: To qualitatively evaluate the systematic implementation of the 'Let Me Decide' advance care directive and palliative care education programme in three long- term care sites Methods: Focus groups were conducted with staff from the homes (n = 17). The sample consisted of 15 Clinical Nurse Managers and two Directors of Nursing. A semi-structured topic guide was used to direct the questions and these addressed the implementation process, challenges implementing advance care planning, advantages/disadvantages and recommendations for the future. Results: Five key categories were presented, with 16 corresponding subcategories. These subcategories emerged as a result of 37 codes. Key benefits of the programme ranged from enhancing communication, changing the care culture, promoting preference-based care and avoiding crisis decision-making. Establishing capacity among residents and indecision were among the main challenges reported by staff. A number of recommendations were proposed by participants and included a multi-disciplinary team involvement, and a blended approach to education. Conclusion: The LMD-ACP has transcended a number of care issues in the homes. Relationships with residents have deepened, a more open and honest environment with family was created, EOL care is now focused on symptom management, comfort and addressing spiritual care needs as opposed to crisis decision making and family conflict.